TARI NUGAL DI DESA TANJUNG KUPANG KECAMATAN TEBING TINGGI KABUPATEN EMPAT LAWANG: TINJAUAN KOREOGRAFI - Ukie Winaranti; Indrayuda Indrayuda; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2014)
ABSTRACT This article aimed at figuring out and describing that the Nugal dance was a creation dance made by using the choreography approach. The desigh of this research was descriptive qualitative research. The object of the research was the Nugal dance at Desa Tanjung Kupang Kecamatan Tebing Tinggi Kabupaten Empat Lawang. Data were obtained from the library study, observation, interview, and documentation. It was found that there were elements of choreography in the Nugal dance. They were the dancers, the movements, the top and floor designs, the group compositions, the costumes, the dance accompaniments, and the ideas and settings of the dance as well as the dance patterns which were seen from the movements and the expressions of the dancers. As a result, the creator of the dance made the dance by using the choreography planning because the dance derived from the farming activities of the society which was also known as Nugal. The dance idea started from the traditional dance called the Kekok dance. New movements were then created into a new form of dance. Keywords : Choreography, and the Nugal Dance.